Asset Meltdown: Fact or Fiction? - Marcel Marekwica; Raimond H. Maurer; Steffen Sebastian (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2006)
This paper analyzes the relation between demographic structure and real asset returns on treasury bills, bonds and stocks for the G7-countries (United States, Canada, Japan, Italy, France, the United Kingdom and Germany). A macroeconomic multifactor model is used to examine a variety of different demographic factors from 1951 to 2002. There was no robust relationship found between shocks in demographic variables and asset returns in the framework of these models, which suggests that Asset Meltdown is rather fiction than fact.
Keywords: G12; J14; G15; 330